Group C Streptococcal Endocarditis Presenting as Clinical Meningitis: Report of a Case and Review of the Literature - Allen R Huang; Dalius J Briedis (Canadian Journal of Infectious Diseases)
Lancefield group C streptococci are known to be pathogenic in a number of animal species, but cause human disease much less commonly than do streptococci of scrogroups A or B. Reported cases of bacteremic infection, pneumonia or meningitis in humans have been very severe with a grave prognosis. The authors describe a patient who presented with classic clinical and laboratory evidence of bacterial meningitis which proved to be a complication of endocarditis caused by a group C streptococcus. This is the first reported case in which meningitis was the presenting manifestation of group C streptococcal endocarditis and is only the second case in which group C streptococcal meningitis and endocarditis have been associated in the same patient. A total of 13 cases of group C streptococcal meningitis have now been reported in the medical literature. Five of these patients died, and four others recovered only to be left with neurological sequelae. The current case confirms the seriousness of group C streptococcal infections in humans. Such infections are associated with a poor prognosis despite apparently adequate antimicrobial therapy.